A Comparison of Ultrasound Imaging Texture Analyses During the Early Postpartum With the Mode of Delivery. (February 2023) - Lee, Hyun Kyoung; Joo, Eunwook; Kim, Seongbeen; Cho, Iseop; Lee, Kyong-No; Kim, Hyeon Ji; Kim, Bohyoung; Park, Jee Yoon
Background: Breastfeeding is beneficial to infants. However, cesarean section is reported to be a risk factor for unsuccessful breastfeeding. Research Aims: (1) To extract discriminating data from texture analysis of breast ultrasound images in the immediate postpartum period; and (2) to compare the analysis results according to delivery mode. Methods: A cross-sectional, prospective non-experimental design with a questionnaire and observational components was used. Participants ( N = 30) were women who delivered neonates at a center from September 2020 to December 2020. The participants underwent ultrasound examination of bilateral breasts 7–14 days after delivery. Ultrasound images were collected for texture analysis. A questionnaire about breastfeeding patterns was given to the participants on the day of the ultrasound examination. Results: No significant differences were found in texture analysis between the breasts of participants who had undergone Cesarean section and vaginal deliveries. The mean volume of total human milk produced in 1 day was significantly greater in the vaginal delivery group than in the cesarean section group ( M = 350.87 ml, SD = 183.83 vs. M = 186.20 ml, SD = 184.02; p = .017). The pain score due to breast engorgement measured subjectively by participants was significantly lower in the vaginal delivery group than in the cesarean section group ( M = 2.8, SD = 0.86 vs. M = 3.4, SD = 0.63; p = .047). Conclusion: Texture analysis of breast ultrasound images did not demonstrate difference between the cesarean section and vaginal delivery groups in the immediate postpartum period; nevertheless, cesarean section was independently associated with less successful breastfeeding.